MicroRNA Profile of MA-104 Cell Line Associated With the Pathogenesis of Bovine Rotavirus Strain Circulated in Chinese Calves - Elkady, Gehad; Chen, Yingyu; Hu, Changmin; Chen, Jianguo; Chen, Xi; Guo, Aizhen (Frontiers in Microbiology, 2022)
Bovine Rotavirus (BRV) causes massive economic losses in the livestock industry worldwide. To elucidate the pathogenesis of BRV would help to develop more effective measures to control BRV infection. MA-104 cell line is sensitive to BRV and thereby a convenient tool to reveal BRV–host interactions. So far, the role of miRNAs of MA-104 cells during BRV infection is still ambiguous. In our approach, we performed Illumina RNA sequencing analysis of miRNA libraries of BRV-infected and mock-infected MA-104 cells at different time points 0 hpi (just after 90 min of adsorption), 6 hpi, 12 hpi, 24 hpi, 36 hpi and 48 hpi, and the total clean reads 74701041 and 74184124 were obtained from BRV-infected and uninfected cells, respectively. From these findings, 579 categorized as known miRNAs and 144 as novel miRNAs. 160 differentially expressed (DE) miRNAs in BRV-infected in comparison to uninfected MA-104 cells were successfully investigated, 95 upregulated, while 65 downregulated. The target mRNAs of DE miRNAs were expected by bioinformatics. The functional annotation of the target genes by GO and KEGG suggested that they were mainly contributed to biological pathways, endocytosis, apoptotic process, trans-Golgi membrane and lysosome. Besides, the mTOR (mml-miR-486-3p and mml-miR-197-3p), NF-κB (mml-miR-204-3p, novel_366), Rap 1 (mml-miR-127-3p), cAMP (mml-miR-106b-3p), MAPK (mml-miR-342-5p) ,T cell receptor signaling pathway (mml-miR-369-5p), RIG-I-like receptor signaling pathway (mml-miR-504-5p), AMPK (mml-miR-365-1-5p), PI3K-Akt (mml-miR-299-3p) signaling pathways were enriched. What is more, real-time qPCR verified the expression pictures of 23 selected DE miRNAs, which were consistent with the results of the deep sequencing, and 28 from their corresponding target mRNAs mainly of regulatory pathways of the cellular machinery and immune importance, according to the bioinformatic analysis. Our study is the first novel approach which uncovers the impact of BRV infection on miRNA expression of MA-104 cells, and it offers clues for identifying potential candidates for antiviral or vaccine strategies.